Representing of Green Building Through the Vital Lens: 10 Years of Diamond Building - Ng, Yan Chi (2020)
Green Building is a very famous topic in advanced country such as USA, Japan, Europe and Australia. Since 20 years ago, they had started to develop green building. Malaysia is still in early state although had recently launched of GBI. However, a Green Building was once an immediate claim to fame. Now, Green Building become the rule rather than an exception. The main highlighted of Green Building are innovative technologies and new construction techniques. It is to carry the promise of improving green and efficiency across the entire value chain of the building. Green Building concept not only for the design stage but also include the operation stage and the end of life stage of a building. The concepts of benefit in term of value may influenced by interests, return and stakeholders which leave a fragmented impression. This paper will discuss the benefit of Green Building through the Diamond Building. The benefits are through the cost saving by energy efficiency and water efficiency and satisfaction level of occupant of Green Building. In carrying out this study, the methodologies used are site observation conducted through visits to the building, interviews with the person in charge and survey the users of the building. The analysis is then made base on the effectiveness of the various energy and water conserving strategies implemented. In conclusion, through Diamond Building had found that the cost saving is one of the best benefit for Green Building although the building had function around 10 years. Furthermore, the occupants in Diamond Building are satisfied with the facilities that design as Green Building. Lastly, this paper only provides a useful reference to the field of green design in tropical climate.